1981
DOI: 10.1104/pp.67.4.763
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in Fescue

Abstract: Chloroplasts isolated from taDl fescue, Festuca arwudinacea Schreb., showed high rates of electron transport, comparable to rates observed for spinach chloroplasts.Chloroplasts were weDl coupled and rates of electron transport from water to methyl viologen (photosystem II and I) were increased two to five times when ADP and inorganic phosphate or methylamine (uncoupler) were added to the reaction mixture. Ratios of P:2e for photosystem II plus I were found to be near 1.2. Electron transport rates from water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Clones of selected tall fescue genotypes were vegetatively propagated from tillers and placed into 4-inch pots for growth chamber and greenhouse studies. Plant material grown in the growth chamber was kept at a 14-h (400 ,uE m 2 s-1), 25 was cut from young, fully expanded leaves as previously described (14). Chl content and Chl a to Chl b ratios were determined by extraction in 80%1o acetone, and absorption was measured on a Perkin-Elmer 552 spectrophotometer, as described by Arnon (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clones of selected tall fescue genotypes were vegetatively propagated from tillers and placed into 4-inch pots for growth chamber and greenhouse studies. Plant material grown in the growth chamber was kept at a 14-h (400 ,uE m 2 s-1), 25 was cut from young, fully expanded leaves as previously described (14). Chl content and Chl a to Chl b ratios were determined by extraction in 80%1o acetone, and absorption was measured on a Perkin-Elmer 552 spectrophotometer, as described by Arnon (2).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work (14), we have shown that isolated chloroplasts from hexaploid tall fescue can exhibit high rates of chloroplast electron transport and phosphorylation. Here, we compare the commonly cultivated hexaploid to a polyploid series of tall fescue with nuclear chromosome number of 14 in the diploid through chromosome number 70 in the decaploid.…”
mentioning
confidence: 99%
“…was originally collected to study photosynthesis potential in wild tall fescue relatives varying in polyploidy (18, 22,26,28). We examined the light-driven reactions in the chloroplast thylakoids using this series (21,22). After screening many genotypes at all polyploid levels (2N = 2X = 14 chromosomes through 2N = lOX = 70 chromosomes), we observed no direct.effect on photosynthetic electron transport as chromosome number varied (22 P70.…”
mentioning
confidence: 99%
“…was originally collected to study photosynthesis potential in wild tall fescue relatives varying in polyploidy (18,22,26,28). We examined the light-driven reactions in the chloroplast thylakoids using this series (21,22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation